Seismic vulnerability overview of historical masonry churches in Europe - Lourenço, Paulo B. (2005)
This paper presents a contribution for the safety assessment of historical masonry churches located in earthquake prone areas. Six different simplified safety indexes (three in-plane and three out-of-plane) are analyzed, taking into account a large sample of forty-four European churches. The sample of buildings has been organized according to the seismic hazard. All in-plane indexes are compared with proposed thresholds, in order to detect cases in serious risk and to define priority of studies. These indexes do not present a clear tendency with respect to seismicity, though a slightly trend can be established. Even for low seismicity areas, in-plane indexes are often violated. Based on the results achieved, a proposal for the usage of the simplified indexes is made. The analysis of the out-of-plane indexes illustrates that a logical common trend with respect to seismicity can be found, which points out the possibility of defining threshold criteria, as used for the in-plane indexes. The results indicate that valuable information can be obtained from simplified methods, with respect to performing a first screening and to prioritizing further deeper investigations.